An unusually sculptured new species of Phreatodrobia Hershler & Longley (Mollusca: Caenogastropoda: Cochliopidae) from central Texas - Alvear, Dominique; Diaz, Peter H.; Gibson, J. Randy; Jones, Mary; Perez, Kathryn E. (Zootaxa, 2020)
There are eight described species in Phreatodrobia, minute, phreatic (subterranean aquatic) snails, all stygobitic and endemic to the Edwards-Trinity Aquifer System of Texas. Two species were described from river drift (Pilsbry & Ferriss 1906) and the others more recently by sampling the water flowing from wells or springs (Hershler & Longley 1986b; Hershler & Longley 1987). Recent sampling from spring orifices and the hyporheic zone of streams have extended the known ranges of the phreatic snails of the region and encountered unknown snails (Alvear et al. 2020). Here we describe Phreatodrobia spica n. sp., a rarely encountered species with a large range of about 400 km (Figure 1). We find P. spica in samples with a diverse assemblage of phreatic animals including other species of Phreatodrobia, isopods, amphipods, coleopterans, and mites. Phreatodrobia spica is distinguished from congeners using morphological and molecular evidence and is characterized by an elevated, trochiform shell with unique sculpture that include spikes and pustules. It has an open umbilicus and a complete, reflected lip that is sometimes appressed to the body whorl.